POLA BUDAYA PEMBENTUKAN KARAKTER DALAM SISTEM PENDIDIKAN DI JEPANG - Iriyanto Widisuseno (Diponegoro University, 2018)
This study examines the problem of cultural patterns of character formation in the education system in Japan. How do cultural patterns that are practiced in the education system in Japan so as to provide access for the people to be able to manage the basic values of life that are considered noble as a guide and source of orientation for the character formation of students. The interesting here is that the Japanese nation in its acculturation process can harmonize modern values with traditional values that have been believed to be the noble values of the nation.There is a paradoxical cultural pattern, but it can synthesize the process of modernization of life on the basis of the value of conventional Japanese traditions. For other nations such as Indonesia, which are allied to Asian countries, they can view them as unique national cultural events. This study aims to uncover cultural practices and schooling in the education system in Japan that can synthesize modern values with the value of the traditions of the people, so that the Japanese become a developed nation and have strong character. This study uses historical factual methods, and qualitative descriptive analysis. That is, reviewing the facts of the development of the school program and its habituation in the practice of the family life of the students. Then analyze the structure and cultural values contained in each education program and the level of social life in Japanese society. The results of the study show that the education system in Japan prioritizes and respects adab and good behavior rather than values. Focusing on teaching adab to children in the lower classes is more important than testing academic skills. The basis of his view, that at the elementary school level, especially the first three years is not to assess knowledge but to build good behavior. Japanese students only get an exam after stepping on the fourth grade, even though they are only mild tests.